Fresno County Young Lawyers Association Justice George Hopper Memorial Luncheon at Star Palace - Watkins, Howard::::::::: (1982)
Leonard Herr, Hal Bolen II, Herbert Levy, and Gordon Park at check in table 5-line corded telephone on wall